Evaluating Antibacterial Efficacy of Cefiderocol and Cefepime/Taniborbactam Against OXA-48-Like and NDM-Expressing Enterobacterales: An In-Vitro and In-Silico Approach - Mohanraj Gopikrishnan; Sriroopreddy Ramireddy; Yamuna Devi Bakathavatchalam; Rinku Polachirakkal Varghese; D. Thirumal Kumar; Binesh Lal; Abi Manesh; Kamini Walia; Balaji Veeraraghavan; C. George Priya Doss (Current Microbiology, 2025)

Molecular and serological screening of coxiellosis in bovines with reproductive disorders in dairy farms - Neha Parmar; Satyaveer Singh Malik; Manesh Kumar; Jay Prakash Yadav; V.K. Vinod; M.S. Sivaprasad; Brijesh Kumar; Jess Vergis; E.S. Sanjumon; Sukhadeo Baliram Barbuddhe; Deepak Bhiwa Rawool (The Veterinary Journal, 2024)

Enhancement of nutritional quality in maize grain through QTL-based approach - Pardeep Kumar; Ningthai Longmei; Mukesh Choudhary; Mamta Gupta; Bhupender Kumar; B. S. Jat; Bharat Bhushan; Manesh Chander Dagla; Sumit Kumar Aggarwal (Cereal Research Communications, 2024)

Fibrinogen in mice cerebral microvessels induces blood–brain barrier dysregulation with aging via a dynamin-related protein 1–dependent pathway - Partha K. Chandra; Manesh Kumar Panner Selvam; Jorge A. Castorena-Gonzalez; Ibolya Rutkai; Suresh C. Sikka; Ricardo Mostany; David W. Busija (GeroScience, 2023)
We previously reported evidence that oxidative stress during aging leads to adverse protein profile changes of brain cortical microvessels (MVs: end arterioles, capillaries, and venules) that affect mRNA/protein stability, basement membrane integrity, and ATP synthesis capacity in mice. As an extension of our previous study, we also found that proteins which comprise the blood–brain barrier (BBB) and regulate mitochondrial quality control were also significantly decreased in the mice’s cortical MVs with aging. Interestingly, the neuroinflammatory protein fibrinogen (Fgn) was increased in mice brain MVs, which corresponds with clinical reports indicating that the plasma Fgn concentration increased progressively with aging. In this study, protein–protein interaction network analysis indicated that high expression of Fgn is linked with downregulated expression of both BBB- and mitochondrial fission/fusion–related proteins in mice cortical MVs with aging. To investigate the mechanism of Fgn action, we observed that 2 mg/mL or higher concentration of human plasma Fgn changed cell morphology, induced cytotoxicity, and increased BBB permeability in primary human brain microvascular endothelial cells (HBMECs). The BBB tight junction proteins were significantly decreased with increasing concentration of human plasma Fgn in primary HBMECs. Similarly, the expression of phosphorylated dynamin-related protein 1 (pDRP1) and other mitochondrial fission/fusion–related proteins were also significantly reduced in Fgn-treated HBMECs. Interestingly, DRP1 knockdown by shRNA(h) resulted in the reduction of both BBB- and mitochondrial fission/fusion–related proteins in HBMECs. Our results suggest that elevated Fgn downregulates DRP1, leading to mitochondrial-dependent endothelial and BBB dysfunction in the brain microvasculature.

Comparative transcriptome analysis of spleen of Newcastle Disease Virus (NDV) infected chicken and Japanese quail: a potential role of NF-κβ pathway activation in NDV resistance - Manesh Kumar Panner Selvam; Vijayrani Kanagaraj; Kumanan Kathaperumal; Ruth H. Nissly; Janet M. Daly; Suresh V. Kuchipudi (VirusDisease, 2023)

Molecular Investigation of the Status of Ticks on Infected Cattle for Coxiella burnetii in India - Pankaj Dhaka; Satya Veer Singh Malik; Jay Prakash Yadav; Srikant Ghosh; Manesh Kumar; Sukhadeo B. Barbuddhe; Deepak B. Rawool (Acta Parasitologica, 2020)

Efficacy of Indolicidin, Cecropin A (1-7)-Melittin (CAMA) and Their Combination Against Biofilm-Forming Multidrug-Resistant Enteroaggregative Escherichia coli - Jess Vergis; S. V. S. Malik; Richa Pathak; Manesh Kumar; R. Sunitha; S. B. Barbuddhe; Deepak B. Rawool (Probiotics and Antimicrobial Proteins, 2020)

Evaluating the efficacy of LaSota vaccination induced protection in chickens upon challenge with a genotype IV strain of Newcastle disease virus - S. Bhuvaneswari; K. G. Tirumurugaan; P. Venkatesan; P. Manesh Kumar; K. Kumanan (VirusDisease, 2017)